2016
DOI: 10.1038/srep39098
|View full text |Cite
|
Sign up to set email alerts
|

Redox properties of extracellular polymeric substances (EPS) from electroactive bacteria

Abstract: Although the capacity for electroactive bacteria to convert environmental metallic minerals and organic pollutants is well known, the role of the redox properties of microbial extracellular polymeric substances (EPS) in this process is poorly understood. In this work, the redox properties of EPS from two widely present electroactive bacterial strains (Shewanella oneidensis and Pseudomonas putida) were explored. Electrochemical analysis demonstrates that the EPS extracted from the two strains exhibited redox pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(32 citation statements)
references
References 38 publications
(45 reference statements)
2
30
0
Order By: Relevance
“…This EPS seems to be quite helpful for cell‐to‐cell and cell‐to‐anode surface adherence. Redox properties of EPS produced by electroactive Shewanella oneidensis and Pseudomonas putida were explored previously . EPS helps in biofilm formation and increasing the surface area for the electron transfer from bacterial cell to anode.…”
Section: Resultsmentioning
confidence: 60%
“…This EPS seems to be quite helpful for cell‐to‐cell and cell‐to‐anode surface adherence. Redox properties of EPS produced by electroactive Shewanella oneidensis and Pseudomonas putida were explored previously . EPS helps in biofilm formation and increasing the surface area for the electron transfer from bacterial cell to anode.…”
Section: Resultsmentioning
confidence: 60%
“…EET process mediated by redox shuttles is an important microbial electron transfer pathway due to the presence of extracellular polymeric substances (EPS), which contain electron transport species in the gap between cells and electron acceptor/donor substances (Marsili et al 2008; Xiao et al 2017). In this sense, it has been reported that EPS from electroactive microorganisms exhibit redox activity due to the presence of proteins, humic substances, flavins and c-type cytochrome enzymes, serving as electron transfer mediators in EPS (Cervantes et al 2007; Flemming et al 2007; Marsili et al 2008; Li et al 2016b; Xiao et al 2017). The redox properties of EPS play an important role in the redox conversion of pollutants, such as U(VI) (Canstein et al 2008; Cao et al 2011), nitrobenzene (Wang et al 2013) and azo dyes (Kudlich et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Many components of EPS, such as DNA, humic acids, and some proteins, are redox-active or conductive/semiconductive ( 16 ). Some studies have shown that EPS are able to synthesize metal nanoparticles in the presence of c-type cytochromes ( 17 ) and have redox properties similar to MR-1 ( 18 ). However, it is poorly understood whether EPS are directly involved in EET processes, because previous microbial EET studies were only conducted on biofilms with EPS retained or on cells from the log stage or early steady stage cultures with little EPS.…”
Section: Introductionmentioning
confidence: 99%